AGILE METHODOLOGIES AND THEIR IMPACT ON SOFTWARE PROJECT SUCCESS WITH CASE STUDIES - Shah, Deepali (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Agile methodologies have revolutionized software development by emphasizing flexibility, collaboration, and iterative progress. This paper explores the impact of Agile methodologies on software project success by examining their principles, comparing them to traditional methodologies, and analyzing empirical evidence of their effectiveness. The study aims to provide a comprehensive understanding of how Agile practices influence project outcomes, with a focus on project performance, stakeholder satisfaction, and team dynamics.